Regional blocks for pain control at the end of life in pediatric oncology - Cuviello, Andrea; Cianchini de la Sota, Ashley; Baker, Justin; Anghelescu, Doralina (Frontiers in Pain Research, 2023)
Background Pain management at the end of life is a fundamental aspect of care and can improve patients' quality of life. Interventional approaches may be underutilized for pediatric cancer patients. Objective To describe a single institution's 10 years of experience with regional pain management at the end of life in pediatric oncology. Methods A retrospective cohort study of 27 patients with pediatric cancer who died between April 2011 and December 2021 and received continuous nerve block (CNB) catheters or single-shot nerve blocks (SSBs) during their last three months of life. The type of blocks, analgesic efficacy, and palliative care involvement were evaluated. Results Twenty-two patients (81.5%) had solid tumor diagnoses, including carcinomas, sarcomas, and neuroblastoma. Most (59%) patients received CNB catheters, and 12 patients (44%) received SSBs for pain control. The mean pain score decreases for CNB catheters and SSBs after interventions were −2.5 and −2.8, respectively, on an 11-point scale. Decreases in opioid patient-controlled analgesia dosing requirements were noted in 56% of patients with CNB catheters; likewise, in 25% of patients with SSBs at 24 h and in 8% at 5 days after interventions. Nearly all patients had PC involvement and received care from pain specialists (96% and 93%, respectively). Twenty-three (85%) had physician orders for scope of treatment orders completed before death. Conclusion Regional pain control interventions can be effective and safe for relieving regional pain and suffering in dying children and young adults. The collaboration between palliative care and pain management specialists at the end of life can help alleviate suffering and improve quality of life.